Guillain-Barré syndrome. - Fonseca, Teresa (2004)
Guillain-Barré syndrome (GBS) is an autoimmune disease that leads to an axonal demyelination and/or degeneration of peripheral nerves through molecular mimicry. The usual pattern is an ascending areflexic motor paralysis with a distinct cerebral-spinal fluid (CSF) showing elevated protein level without accompanying pleocytosis. Diagnosis is essentially clinical, but the CSF studies and electrodiagnostic features may help confirming the diagnosis. Prognosis is usually good, with complete recovery in 80-85% of the cases. However, 10% will remain with permanent neurological damage and about 5% will die. Immunomodulation is the goal treatment, but supportive care is of the utmost importance in the treatment and prevention of complications. The purpose of this work was to review all GBS diagnosed between 1st January 1997 and 31st December 2001, in patients 18 or older admitted to Hospital Pedro Hispano (Portugal). During the 5-year study period, 62446 patients were admitted to hospital, of which 15 with GBS. Thirteen had a good evolution: 10 with total recovery over a period of a maximum of six months; one remain with serious neurological damage at 2 years of evolution and the remaining one died with a pure motor form of GBS (both had a previous gastrointestinal infection). The results of this review are in accordance with what is described in the literature, regarding incidence, epidemiological data and clinical behaviour.